1992
DOI: 10.1016/0735-1097(92)90269-s
|View full text |Cite
|
Sign up to set email alerts
|

Early revascularization improves survival in cardiogenic shock complicating acute myocardial infarction

Abstract: The effects of coronary revascularization by percutaneous transluminal coronary angioplasty or coronary bypass grafting, or both, on survival were evaluated in 81 patients with cardiogenic shock complicating acute myocardial infarction. Thirty-two patients had successful revascularization and 49 patients had unsuccessful or no revascularization. Revascularization was achieved by coronary angioplasty in 22 patients, coronary bypass surgery in 2 and angioplasty followed by bypass surgery in 8. No significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(46 citation statements)
references
References 41 publications
1
43
0
2
Order By: Relevance
“…The trial was designed in the early 1990s in the context of a high mortality rate among patients with cardiogenic shock, as well as reported reductions in mortality of 30 percent or more among patients undergoing angioplasty or coronary-artery surgery in nonrandomized series. [5][6][7][8][9][10][11][12][13][14][15] These large reductions clearly reflected bias related to selection for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was designed in the early 1990s in the context of a high mortality rate among patients with cardiogenic shock, as well as reported reductions in mortality of 30 percent or more among patients undergoing angioplasty or coronary-artery surgery in nonrandomized series. [5][6][7][8][9][10][11][12][13][14][15] These large reductions clearly reflected bias related to selection for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Nonrandomized studies report markedly lower mortality rates among patients who have undergone revascularization for shock. [5][6][7][8][9][10][11][12][13][14][15][16] However, selection bias is evident. 17,18 In small series of patients undergoing early primary angioplasty for cardiogenic shock, in-hospital mortality rates ranged from 26 percent to 72 percent.…”
Section: Discussionmentioning
confidence: 99%
“…9) Moreover, Moosvi, et al reported that early revascularization, particularly within 24 hours from the onset of cardiogenic shock, improved survival in patients with cardiogenic shock complicating acute myocardial infarction. 10) However, of 4 patients with cardiogenic shock who had successful angioplasty within 6 hours, 3 patients (75%) died during hospitalization. Overall, 5 of 6 patients (86%) with cardiogenic shock died during hospitalization.…”
Section: History Of Patients: Group S Had a Greater Prevalence Of Prementioning
confidence: 99%
“…We retrospectively compared the clinical background, coronary risk factors, angiographic findings, acute results of primary PCI, and in-hospital prognosis between primary PCI-treated patients requiring mechanical support devices during primary PCI and/or admission period (with-IABP/PCPS group, n=275) and those without mechanical support devices (without-IABP/PCPS group, n=1,510). The diagnosis of AMI required the presence of 2 of the following 3 criteria: (1) characteristic clinical history; (2) serial changes on the ECG suggesting infarction (Q-waves) or injury (ST-segment elevations); and (3) transient increase in cardiac enzymes to more than 2-fold the normal laboratory value.…”
Section: Patient Populationmentioning
confidence: 99%